Comparison Between Modified Lateral Arm Free Flap and Traditional Lateral Arm Free Flap for the Reconstruction of Oral and Maxillofacial Soft Tissue Defects - Wang, Wei-Ming; Sun, Lu; Yang, Si-Si; Hu, Shu-Jun; Zuo, Yi-Jie; Min, An-Jie (Frontiers in Oncology, 2022)
OBJECTIVE: The traditional lateral arm free flap (tLAFF) has the disadvantages of short vascular pedicle, small vascular diameter and non-perforator flap. We used a new method to prepare modified LAFF (mLAFF) and evaluate its application value in the repair of oral and maxillofacial soft tissue defects. METHODS: The anatomical features of the flap were recorded and compared between tLAFF group and mLAFF group. All the flaps in the modified group were perforator flaps. Statistical analysis was performed on the data using ANOVA on SPSS 22.0 statistical software package. RESULTS: Forty-five mLAFFs were prepared as eccentric design rotation repair perforated flap, multi-lobed or chimeric perforator flaps. Compared with the tLAFF, the vascular pedicle length of the mLAFF was increased, and the outer diameter of the anastomosis was thickened. The damage to the donor site was less. The difference was statistically significant. CONCLUSION: The mLAFF can effectively lengthen the vascular pedicle length and increase the anastomosis diameter. Perforator LAFF in the repair of oral and maxillofacial defects have good application value.